Effect of voltage on colloidal gold (Au) nanoparticles produced using electro-dissolution-reduction method - Haiza, Haroon; Yaacob, Iskandar Idris; Ahmad Azhar, Ahmad Zahirani (Trans Tech Publications, Switzerland, 2015)
Colloidal gold nanoparticles have been successfully prepared using a simple two-electrode cells connected to a DC power supply. During the electro-dissolution-reduction process, the bulk gold at the anode oxidized into gold cations which then reacted with the chloride ions to form aurochloride complex. The complex ions were then reduced by the citrate ion to form colloidal gold nanoparticles. The size and shape of the nanoparticles were modulated by varying the terminal voltages. The colloidal gold nanoparticles obtained were characterized by field-emission scanning electron microscope (FESEM), transmission electron microscope (TEM) and ultraviolet-visible spectrophotometer (UV-Vis). From FESEM analysis, it was found that by increasing the voltage, the size of colloidal gold nanoparticles produced marginally decreased. The mean sizes of gold nanoparticles were roughly about 23.5 nm, 23.2 nm and 19.3 nm for 32 V, 36 V and 40 V, respectively. TEM micrograph showed that the shape of gold nanoparticles obtained is almost spherical. The characteristic peaks of UV-Vis spectra revealed that the suspension was indeed colloidal gold nanoparticles.